Cumulative Climate Shocks and Migratory Flows: Evidence from Sub-Saharan Africa - Salvatore Di Falco; Anna B. Kis; Martina Viarengo (Center for Economic Studies and ifo Institute (CESifo), 2022)
We re-examine the effects of negative weather anomalies during the growing season on the decision to migrate in rural households in five sub-Saharan African countries. To this end we combine a multi-country household panel dataset with high-resolution gridded precipitation data. We find that while the effect of recent adverse weather shocks is on average modest, the cumulative effect of a persistent exposure to droughts over several years leads to a significant increase in the probability to migrate. The results show that more frequent adverse shocks can have more significant and long-lasting consequences in challenging economic environments.
Keywords: O15; O13; Q54; 330; climate shocks; rural-urban migration; economic development